Pengelolaan Program Praktik Kerja Lapangan dalam Meningkatkan Kompetensi Bermasyrakat pada Peserta Didik di Madrasah Aliyah Ash-Shiddiqi Putri Jember. - Rahmah, Erline rofiatur (Program Studi Manajemen Pendidikan Islam, 2023)
Madrasah Aliyah Ash-Shiddiqi Putri Jember which is an educational institution characterized by Islamic religion, namely a strong pesantren culture. Madrasah Aliayah Ash-Shiddiqi Putri Jember tries to train the students to develop their talents and desires, improve social, and prepare themselves for society. It can be seen from the field work practice program which aims to increase students who are sociable. In this case, there are three main issues that become the focus of research, namely, (1) planning the management of field work practice programs in improving the competence of socializing students in Madrasah, (2) implementing the management of field work practice programs in improving the competence of socializing students in Madrasah, and (3) evaluating the management of field work practice programs in improving the psychomotor competence of socializing students in Madrasah. The three research focuses also answer the research objectives. This research uses descriptive research with a case study research design. This research used non-participant observation, semi-structured interviews, and documentation as data collection techniques. Data were analyzed using data reduction, data presentation and data verification. Meanwhile, data validity can be seen from triangulation of techniques and sources. Based on the research findings, it can be concluded that the field work practice program in improving social competence in students at MA Ash-Shiddiqi Putri Jember is in the form of teaching practice, skill practice and social practice. (1) Planning can be seen from the formulation of the vision, mission, goals of the madrasah and the formulation of the madrasah work plan. (2) Implementation can be seen from madrasah guidelines, madrasah organizational structure, and implementation of madrasah activities. (3) Evaluation can be seen from four components, namely the input component, process component, output component, and outcome component